Influence of farmers’ practices on fall armyworm infestation levels in maize fields (Makerere University Journal of Agricultural & Environmental Sciences, 2022)
The fall armyworm (FAW) (Spodoptera frugiperda) is an economically important recently introduced pest that is threatening maize production in sub-Saharan Africa. This study aimed to investigate the effect of current smallholder crop production practices on fall armyworm infestation in Uganda. A survey of 87 farms was conducted in cropping systems categorised as: maize monocrop (20 farms), maize+bean intercrop (18), maize+soybean intercrop (19), maize+cassava intercrop (20), and maize mixed with two or more companion crops (10). These were from the districts of Iganga (n=29), Mayuge (n=30) and Namutumba (n=28). The other management practices considered were pesticide application, intercropping intensity, and maize variety grown. Results indicated that FAW incidence of damage in farmers’ fields ranged from 64.5 to 99.1%, with moderate severity scores. Namutumba district had the highest incidence and severity whereas Iganga had the lowest. Pesticide application frequency and intercropping system interacted significantly to reduce FAW infestations; as did local varieties, and high intercropping intensity. The multi-crop (>3 crops) system had the lowest FAW infestation, and Maize+bean intercrop edged the other individual companion crop intercrops in lowering infestation by the FAW. These results provide a foundation for building an integrated pest management system for the FAW in Uganda
Keywords: Cropping systems; intercropping intensity; pesticide usage; Spodoptera frugiperda; variety